Habitat Preferences of Blue Swimming Crab (Portunus pelagicus) Species Complex - Asphama, Andi Ivo; Amir, Faisal; Malina, Asmi Citra; Fujaya, Yushinta (Indonesian Aquaculture Society (MAI), 2015)
Blue swimming crabs (Portunus pelagicus) from Makassar Strait have some variations in color and pattern of spots on the carapace. The purpose of this study was to analyze the habitat preferences blue swimmer crab species complex from Macassart Straits. Crabs were grouping based on the difference of color and pattern of spots on the crab carapace to identify the variety of crabs. Habitat was observed salinity, depth, and substrate type. The results of PCA analysis showed a tendency of each population occupies a different base substrates (P<0.01). Substrate type also correlated with depth and salinity. The conclusion of this study is the difference in the color and pattern on the carapace thought to be different species or varieties and they occupy different habitats. Preferences of the different habitats for different population groups are very important information for the development of blue swimming crab aquaculture in the future. Keywords: Crab, Portunus pelagicus, morphometric, habitat, aquaculture